RASON promotes KRASG12C-driven tumor progression and immune evasion in non-small cell lung cancer - Jianzhuang Wu; Kexin Xie; Yixuan Zhang; Weiyi Zhang; Rongjie Cheng; Yaliang Zhang; Yugui Xia; Tongyan Liu; Rong Yin; Yudong Qiu; Tao Xu; Rutian Li; et al. (Journal of Experimental & Clinical Cancer Research)
Abstract Background KRAS is the most frequently mutated oncogene in human cancers, with KRASG12C being a prevalent driver mutation in 12–13% non-small cell lung cancer (NSCLC) cases. Despite breakthroughs in KRASG12C inhibitors such as sotorasib (AMG-510) and adagrasib (MRTX-849), clinical resistance remains a challenging issue, highlighting the need for deeper understanding of the molecular mechanisms underlying KRASG12C-driven oncogenic signaling in NSCLC. Previously, we identified RASON as a novel regulator of KRASG12D/V signaling in pancreatic cancer. Herein, we aim to explore the role of RASON in KRASG12C-driven NSCLC and its therapeutic potential. Methods Immunohistochemistry analysis of NSCLC patient cohorts was performed to demonstrate the correlation between RASON expression and NSCLC progression. Immunoblotting was performed to evaluate the effects of RASON on KRASG12C downstream signaling. In vitro and in vivo assays including cell proliferation, sphere formation, tumor implantation and genetic mouse models were performed to determine the oncogenic role of RASON. RNA-seq analysis was utilized to identify the key signaling pathway regulated by RASON. Immunofluorescence, immunoprecipitation, nuclear magnetic resonance and biochemistry assays were used to validate the interaction between KRASG12C and RASON. Phagocytosis assay and flow cytometry were conducted to explore the effects of RASON on the tumor immune microenvironment. Pharmacological inhibition in subcutaneous xenograft model was used to determine the therapeutical potential of RASON. Results RASON is overexpressed in NSCLC with KRASG12C mutation and correlates with poor patient prognosis. Genetic knockout of RASON significantly reduced lung tumor burden in LSL-KRASG12D; Trp53R172H/+ mice. In KRASG12C-mutant lung cancer cell lines, RASON overexpression enhanced, while CRISPR-mediated knockout suppressed, both in vitro proliferation and in vivo tumor growth. Mechanistically, RASON directly binds KRASG12C, stabilizes it in the GTP-bound hyperactive state and promotes downstream signaling. RASON knockout significantly reduced CD47 expression, enhancing macrophage-mediated phagocytosis and anti-tumor immunity. Therapeutically, antisense oligonucleotides targeting RASON not only exhibited tumor-suppressive effects, but also synergized with the KRASG12C inhibitor AMG-510 to significantly enhance anti-tumor efficacy. Conclusion This study reveals RASON as a key oncogenic regulator of KRASG12C signaling, driving lung tumorigenesis and progression, and identifies RASON as a promising therapeutic target for KRASG12C mutant non-small cell lung cancer.